Field hospital wastewater treatment scenario - Khan, Nadeem Ahmad; Ahmed, Sirajuddin; Vambol, Sergij; Vambol, Viola; Farooqi, Izharul Haq (Ecological Questions, 2019)
In extreme situations with a large number of victims, field hospitals are deployed to provide patients with medical treatment. The large number of patients with different types of medications used generates the problem of hospital waste accumulation, including hospital wastewater (HWW). Wastewater is water having compromised characteristics that adversely affect the environment. Many countries do not have strict regulations regarding the disposal of hospital effluent, which contains pathogens, toxic chemicals and radioisotopes. The disposal of such substances poses a serious threat to public health and the environment. This paper discusses the possibilities of field hospital wastewater management development. Micropollutants, including pharmaceuticals, are found in different ecosystem elements, like soil, surface and ground water, drinking water as well as treated effluent from conventional wastewater treatment plants. Wastewater discharged from different health facilities, with varying concentrations of pharmaceuticals, is often mixed with municipal sewage, thus remains untreated even after passing through conventional treatment plants. Extensive experience in the application of different types of HWW treatment methods allows the development of an optimal treatment scenario for field hospital wastewater problem resolution, including the combination of Microbiological Reactor and Fenton Process technologies. They are applicable in the case of low wastewater flow rate values, specific for field hospital conditions.